Participants at the colloquium on the Spanish Civil War, Barcelona, Palau dels Congresos, 1979, April 19-21. Doctor Lledó speaking. Left of him E. Giralt i Raventós
Participants at the colloquium on the Spanish Civil War, Barcelona, Palau dels Congresos, 1979, April 19-21. Doctor Lledó speaking. Left of him E. Giralt i Raventós.